2021
DOI: 10.3390/cancers13112517
|View full text |Cite
|
Sign up to set email alerts
|

Case-Control Analysis of the Impact of Anemia on Quality of Life in Patients with Cancer: A Qca Study Analysis

Abstract: Anemia is a common condition in cancer patients and is associated with a wide variety of symptoms that impair quality of life (QoL). However, exactly how anemia affects QoL in cancer patients is unclear because of the inconsistencies in its definition in previous reports. We aimed to examine the clinical impact of anemia on the QoL of cancer patients using specific questionnaires. We performed a post-hoc analysis of a multicenter, prospective, case-control study. We included patients with cancer with (cases) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Self-reported quality of life using EORTC QOL C30 and BDI-S will enable us to gain concrete information about the effect of deterioration of motor function on the patient's quality of life and their emotional health. These questionnaires have been validated in numerous papers addressing quality of life in cancer patients [27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Self-reported quality of life using EORTC QOL C30 and BDI-S will enable us to gain concrete information about the effect of deterioration of motor function on the patient's quality of life and their emotional health. These questionnaires have been validated in numerous papers addressing quality of life in cancer patients [27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is an urgent need to develop preventive strategies to mitigate AR. The prevalence of anemia is estimated to be 24.8% in the general population [4]. Previous epidemiological studies have reported an increased risk of anemia in individuals with allergic disorders [5].…”
Section: Introductionmentioning
confidence: 99%
“…Anemia ranges from causing mild, persistent symptoms like fatigue to life-threatening conditions, especially for individuals with concurrent chronic diseases. Without a doubt, it significantly impairs quality of life (QOL) for cancer patients [5][6].…”
Section: Introductionmentioning
confidence: 99%